2011
DOI: 10.1111/j.1365-2966.2011.19797.x
|View full text |Cite
|
Sign up to set email alerts
|

Optical detection and spectroscopic confirmation of supernova remnant G213.0−0.6 (now redesignated as G213.3−0.4)

Abstract: During a detailed search for optical counterparts of known Galactic supernova remnants (SNRs) using the Anglo‐Australian Observatory/United Kingdom Schmidt Telescope (AAO/UKST) Hα survey of the southern Galactic plane we have found characteristic optical Hα filaments and associated emission in the area of SNR G213.0−0.6. Although this remnant was previously detected in the radio as a non‐thermal source, we also confirm emission at 4850 MHz in the Parkes‐MIT‐NRAO (PMN) survey and at 1400 MHz in the NRAO/VLA Sky… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…This result suggests that SNR G213.0−0.6 is interacting with a clumpy interstellar medium, which agrees with the CO emission near the Hα peak using our CO data (Figure 16). Assuming a constant value of X CO = 2 × 10 20 cm −2 K −1 km −1 s (Bolatto et al 2013), the MC's thickness of 4 ′ , and a distance of 1 kpc (see below), the density of the MC is about 300d −1 1kpc cm −3 , which is consistent with the result of the optical study (Stupar & Parker 2012). The interesting MC, as well as its velocity structure, suggests that the molecular gas with LSR velocity ∼8-11 km s −1 is probably interacting with SNR G213.0−0.6.…”
Section: Snr G2130−06supporting
confidence: 78%
See 2 more Smart Citations
“…This result suggests that SNR G213.0−0.6 is interacting with a clumpy interstellar medium, which agrees with the CO emission near the Hα peak using our CO data (Figure 16). Assuming a constant value of X CO = 2 × 10 20 cm −2 K −1 km −1 s (Bolatto et al 2013), the MC's thickness of 4 ′ , and a distance of 1 kpc (see below), the density of the MC is about 300d −1 1kpc cm −3 , which is consistent with the result of the optical study (Stupar & Parker 2012). The interesting MC, as well as its velocity structure, suggests that the molecular gas with LSR velocity ∼8-11 km s −1 is probably interacting with SNR G213.0−0.6.…”
Section: Snr G2130−06supporting
confidence: 78%
“…We suggest that this feature is probably related to the remnant's shock. Stupar & Parker (2012) found that the density in the region of the Hα peak is relatively high based on optical observations (n e ∼ 10 2 cm −3 , refer to Table 2 in their paper). This result suggests that SNR G213.0−0.6 is interacting with a clumpy interstellar medium, which agrees with the CO emission near the Hα peak using our CO data (Figure 16).…”
Section: Snr G2130−06mentioning
confidence: 99%
See 1 more Smart Citation
“…The nearby TeV source HESS J1858+020 (Aharonian et al 2008c) has been proposed as originating from CRs escaping from the SNR and illuminating nearby clouds (Paron & Giacani 2010). SNR G213.3−0.4: a very low radio surface brightness SNR initially designated as G213.0−0.6 by Reich et al (2003), the SNR identification was later confirmed by optical line observations (Stupar & Parker 2012). The SNR lies near the H II region S284, which is coincident with the γ-ray source 2FGL J0647.7+0032.…”
Section: Galactic Snrsmentioning
confidence: 96%
“…It is a commonly adopted diagnostic (see Fesen et al 1985) that an [SII]/Hα ratio >0.5 can separate SNRs from planetary nebula and HII regions as seen and expected in SNRs (e.g Stupar & Parker 2012). It is clear from Table 1 that the observed [SII]/Hα ratio which ranges from 0.6 to 1.29, is strongly in the shocked regime for all fibres, particu- larly for 2dF fibres 260 and 259 which also happen to be on opposing sides of the optical shell.…”
Section: Aat Aaomega Spectroscopymentioning
confidence: 99%